The Remarkable Environmental Rebound Effect of Electric Cars: A Microeconomic Approach - David Font Vivanco; Jaume Freire-González; René Kemp; Ester van der Voet (Environmental Science & Technology, 2014)
This article presents a stepwise, refined, and practical analytical framework to model the microeconomic environmental rebound effect (ERE) stemming from cost differences of electric cars in terms of changes in multiple life cycle environmental indicators. The analytical framework is based on marginal consumption analysis and hybrid life cycle assessment (LCA). The article makes a novel contribution through a reinterpretation of the traditional rebound effect and methodological refinements. It also provides novel empirical results about the ERE for plug-in hybrid electric (PHE), full-battery electric (FBE), and hydrogen fuel cell (HFC) cars for Europe. The ERE is found to have a remarkable impact on product-level environmental scores. For the PHE car, the ERE causes a marginal increase in demand and environmental pressures due to a small decrease in the cost of using this technology. For FBE and HFC cars, the high capital costs cause a noteworthy decrease in environmental pressures for some indicators (negative rebound effect). The results corroborate the concern over the high influence of cost differences for environmental assessment, and they prompt sustainable consumption policies to consider markets and prices as tools rather than as an immutable background.
Keywords: 330